THE EFFECT OF PROJECT-BASED LEARNING MODELS ON STUDENTS’ LEARNING OUTCOMES ON HIGH PRINT ART MATERIALS FOR FOURTH-GRADE STUDENTS AT SD NEGERI LAMPEUNEURUT ACEH BESAR - Riski Prastiya; Aida Fitri; Fauzi; Novysa Basri; Alfi Syahrin (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
This paper analyzes the significant effect of applying the Project-Based Learning model on students’ learning outcomes on high print art materials at grade IV of SD Negeri Lampeuneurut Aceh Besar. By using a quantitative methodology, the type of experimental research with a pre-experimental design uses one group pretest-posttest design. The research population was the whole fourth-grade students, which consisted of 4 classes with one class sampling using the Nonprobability Sampling or Purposive Sampling technique. Data collection was carried out using tests, which were skill tests with instruments in the form of performance tests in order to measure the students’ initial and final skills. Meanwhile, data analysis techniques used SPSS Statistics version 24 and hypothesis testing with paired sample t-tests, which obtained a significance value (2-tailed) of 0.000 < 0.05. Subsequently, the decision-making criteria were H1 accepted and H0 rejected. In addition, students were able to create innovation in their creativity, and even the project results made by students exceeded the researcher’s expectations. Thus, it can be concluded that there is a significant effect of the use of the Project-Based Learning model on the students’ learning outcomes on high print art materials for fourth-grade students at SD Negeri Lampeuneurut Aceh Besar.